MO182CRYSTALLINE LIGHT CHAIN CAST NEPHROPATHY IS ASSOCIATED WITH EARLY MORTALITY IN PATIENTS WITH MULTIPLE MYELOMA. (29th May 2021) - Lin, Zishan; Zhang, Xu; Yu, Xiaojuan; Wang, Suxia; Cen, Xinan; Zhou, Fude; Zhao, Minghui
Abstract: Background and Aims: Light chain cast nephropathy is the most common paraprotein-associated kidney lesion in patients with multiple myeloma (MM). Rarely, light chain cast nephropathy could show crystalline appearance in patients with multiple myeloma, also known as crystalline light chain cast nephropathy. We here report the first retrospective study of crystalline light chain cast from a single centre. Method: All native kidney biopsies were retrospectively studied in the Peking University First Hospital from 2000 to 2020. Newly diagnosed MM patients with were enrolled. Patients with light chain cast nephropathy at least one cast with crystalline appearance were identified as crystalline light chain cast nephropathy (Figure 1, n = 8), others were identified as ordinary light chain cast nephropathy ( n = 18). Results: The cohort of crystalline light chain cast nephropathy consisted of 6 men and 2 women with a median age of 59.5 (range, 41-73) years. All patients suffered from advanced multiple myeloma (1 with ISS staging II, 7 with ISS staging III) and acute kidney injury with a median eGFR of 5.59 (range, 2.27-26.04) mL/min/1.73m2. All patients except 1 required emergency dialysis at admission. Microhematuria was presented in 3 patients. Median proteinuria was 2.13 (rang, 0.83-3.59) g/24h and median serum albumin was 38.2 (30.7-46.7) g/L. No one presented with nephrotic syndrome. Monoclonal immunoglobulin, detected in all patients on serum protein immunofixation electrophoresis, was λ alone in 5 patients, κ alone in 1 patient, IgG λ in 1 patient, IgA λ in 1 patient. The 8 patients were followed up with a median time of 8 (range, 2-24) months. Three patients received VAD chemotherapy and 5 patients received bortezomib based regimens. At the time of last follow-up, 2 of 7 patients who needed emergency dialysis got rid of dialysis and the rest remained dialysis-dependent. Five patients died with a median time of 5 (range, 2-19) months, 2 patients achieved partial remission and 1 patient achieved complete remission. There was no significant difference in clinical features, treatments and main outcomes between crystalline light chain cast nephropathy patients and ordinary light chain cast nephropathy patients (Table 1 ). However, crystalline light chain cast nephropathy patients had higher early mortality than ordinary light chain cast nephropathy patients (50.0% vs 11.1%, p = 0.03). Conclusion: Crystalline light chain cast nephropathy patients usually presented with acute kidney injury requiring emergency dialysis. Although various types of monoclonal immunoglobulin were detected, there was a dominance of the λ isotype. Compared to ordinary light chain cast nephropathy patients, crystalline light chain cast nephropathy patients had higher early mortality.